Comparison of 68 Ga-DOTATOC-PET/CT and PET/MRI hybrid systems in patients with cranial meningioma: Initial results - Afshar-Oromieh, Ali; Wolf, Maya B.; Kratochwil, Clemens; Giesel, Frederik L.; Combs, Stephanie E.; Dimitrakopoulou-Strauss, Antonia; Gnirs, Regula; Roethke, Matthias C.; Schlemmer, Heinz P.; Haberkorn, Uwe (Neuro-Oncology, 2015)
Background 68 Ga-DOTATOC-PET/CT is a well-established method for detecting and targeting the volume definition of meningiomas prior to radiotherapy. Moreover, there is evidence that this method is able to detect meningiomas with higher sensitivity than the goldstandard MRI. Since the hybrid PET/MRI scanner became available in the past few years, the next stage of development could consequently evolve by evaluating the feasibility of a hybrid PET/MRI scanner using 68 Ga-DOTATOC for detecting meningiomas. Methods Fifteen patients received 68 Ga-DOTATOC-PET/CT (0.5 h post injection [p.i.]) followed by PET/MRI 2 hours p.i. Both investigations were analyzed separately and then compared with respect to image quality, detection of intracranial meningiomas, and radiotracer uptake values (RUVs). In addition, ratios between radiotracer uptake in meningiomas and pituitary glands were compared between both PET/CT and PET/MRI. Results Overall, 33 intracranial meningiomas were detected. All were visible with high contrast in both PET/CT and PET/MRI. 68 Ga-DOTATOC-PET/MRI provided flawless image quality without artefacts. Calculated RUV in meningiomas, as well as the ratios of RUVs in meningiomas to those of pituitary glands, were higher in PET/CT. As a result, meningiomas can be distinguished from pituitary glands better in early images. Conclusions 68 Ga-DOTATOC-PET/MRI provided flawless image quality and presented an ideal combination of high sensitivity/specificity (PET) and the best possible morphological visualization of meningiomas (MRI). In addition, excellent detection of meningiomas is already possible at 0.5 hours p.i. Later images do not improve the distinction between pituitary gland and adjacent meningiomas. However, RUVs need to be carefully compared between both imaging modalities.
CRIS-Team Scopus Importer:2023-03-08
Keywords: 68 Ga-DOTATOC; hybrid imaging; meningioma; MRI; PET/CT; PET/MRI; somatostatin receptor